Microsoft Azure security center - Diogenes, Yuri; Shinder, Thomas W. (Microsoft Corporation : Pearson Education, 2020)
NOW FULLY UPDATED: high-value Azure Security Center insights, tips, and operational solutions Reflecting updates through mid-2019, this book presents comprehensive Azure Security Center techniques for safeguarding cloud and hybrid environments. Leading Microsoft security and cloud experts Yuri Diogenes and Dr. Thomas Shinder help you apply Azure Security Center's robust protection, detection, and response capabilities in key operational scenarios. You'll walk through securing any Azure workload, and optimizing key facets of modern security, from policies and identity to incident response and risk management. Brand-new coverage includes single-click remediation, IoT, improved container security, Azure Sentinel, and more. Whatever your security role, you'll learn how to save hours, days, or even weeks by solving problems in the most efficient and reliable ways possible. Two of Microsoft's leading cloud security experts show how to: Implement a comprehensive new security paradigm designed specifically for cloud and hybrid environments Gain visibility and control to secure all key workloads Incorporate Azure Security Center into your security operations center, and integrate Azure AD Identity Protection Center and third-party solutions Adapt Azure Security Center's built-in policies and definitions for your organization Perform security assessments, and implement Azure Security Center recommendations fast with single-click remediation Use incident response features to detect, investigate, and address threats Create high-fidelity fusion alerts to focus attention on your most urgent security issues Implement application whitelisting and just-in-time VM access Assess IoT device security with the Azure IoT Hub managed service Monitor user behavior and access, and investigate compromised or misused credentials Integrate Microsoft's new Azure Sentinel Security Information and Event Management (SIEM) platform Customize and perform operating system security baseline assessments About This Book For cloud architects, designers, implementers, operations professionals, and security specialists working in Microsoft Azure cloud or hybrid environments For all IT professionals and decision-makers concerned with the security of Azure environments.